QUALITY ASPECTS OF HEALTHCARE DELIVERY TO THE POPULATION OF RUSSIA - Zoubets, Alexey; Novikov, Alexey; Oborsky, Alexey (Revista Inclusiones, 2020)
Subject. The process of improving the quality of life of the Russian population / Study of the real state of the quality of life of the population of Russia. Goals/Objectives. To assess the quality of medical care in the context of improving the quality of life. Methodology. Empirical level research methodology. Results/conclusions. A study of the quality of medical care for the population has been conducted / In terms of the main indicators of the quality of health care for the population, Russia lags behind the economically developed countries of the world.